Total beta-adrenoceptor deficiency results in cardiac hypotrophy and negative inotropy - Lee, S; Grafweg, S; Schneider, T; Jimenez, M; Giacobino, J-P; Ghanem, A; Tiemann, K; Bloch, W; Müller-Ehmsen, J; Schwinger, R H G; Brixius, K (Physiological research, 2010)
The present study investigated cardiac function in hearts of mice with total deficiency of the beta1-, beta2- and beta3-adrenoceptors (TKO) in comparison to wildtype mice (WT). We investigated cardiac morphology and echocardiographic function, measured protein expression of Ca2+-regulatory proteins, SERCA 2a activity, myofibrillar function, and performed running wheel tests. Heart weight and heart-to-body weight ratio were significantly smaller in TKO as compared to WT. This was accompanied by a decrease in the size of the cardiomyocytes in TKO. Heart rate and ejection fraction were significantly diminished in TKO as compared to WT. Protein expressions of SERCA 2a, ryanodine receptor and Na+/Ca2)-exchanger were similar in TKO and WT mice, but phospholamban protein expression was increased. PKA-dependent phosphorylation of phospholamban at serine 16 was absent and CaMKII-dependent phosphorylation at threonine 17 was decreased in TKO. All alterations were paralleled by a decrease in SERCA 2a-activity. A similar maximal calcium-dependent tension but an increased myofibrillar calcium-sensitivity was measured in TKO as compared to WT. We did not observe relevant functional impairments of TKO in running wheel tests. In the absence of beta-agonistic stimulation, SERCA 2a activity is mainly regulated by alterations of phospholamban expression and phosphorylation. The decreased SERCA 2a activity following beta-adrenoceptor deficiency may be partly compensated by an increased myofibrillar calcium-sensitivity.
Keywords: Cyclic AMP-Dependent Protein Kinases; Myocardial Contraction; Phosphorylation; Receptors, Adrenergic, beta-2; Ryanodine Receptor Calcium Release Channel; echokardiografie; fosforylace; Echocardiography; Myofibrils; pumpa pro výměnu sodíku a vápníku; Female; Sodium-Calcium Exchanger; kondiční příprava zvířat; Sarcoplasmic Reticulum Calcium-Transporting ATPases; Receptors, Adrenergic, beta-1; zvířata; myši; kardiomegalie; Mice; myši knockoutované; Cardiomegaly; sarkoplazmatická Ca2+-ATPáza; ženské pohlaví; Mice, Knockout; myofibrily; Physical Conditioning, Animal; kontrakce myokardu; beta-1-adrenergní receptory; proteinkinasy závislé na cyklickém AMP; Animals; beta-3-adrenergní receptory; ryanodinový receptor vápníkového kanálu; Receptors, Adrenergic, beta-3; beta-2-adrenergní receptory